POTENSI STRUKTUR NANO KARBON DARI BAHAN LIGNOSELULOSA KAYU JATI DAN BAMBU - Gustan Pari; Adi Santoso; Djeni Hendra; Buchari; Akhirudin Maddu; Mamat Rachmat; Muji Harsini; Teddi Her anto; Saptadi Darmawan (Jurnal Penelitian Hasil Hutan, 2016)
Nanotechnology research in the realm of forest products can be exploited from lignocellulose into nano carbon. The research was aimed to provide the potency of nano carbon structure from lignosellulose as bioenergy or biosensor material. O The materials of teak wood and bamboo were carbonized into charcoal at 400-500 C followed by activation using O chemical and physical processes at 800 C for 60 minutes. This process produced charcoal with high crystalinity and surface area. After purification and activation, the activated charcoal was subsequently doped process with Zn and Ni metals which O then followed by sintering using spark plasma at 1300 C. The qualities and structure of all the resulting carbon were evaluated using nano scale devices i.e. Pyrolysis Gas Chromatography Mass Spectrometer, Scanning Electron Microscope Energy Diffraction X-ray Spectrometer, X-ray Diffractometer, I-V meter and potensiometer. Results showed that the best activated charcoal produced from the chemical-physical activation (KOH steam) possessed high fixed carbon of 84.29%; 2 surface area of 850.5 m /g, crystallinity of 38,99% and resistancy of 0.10. The teak activated charcoal which intercalated by Ni at ratio of 1:5 produced the best properties with crystallinity degree of 73.45% and conductivity of 433.86 S/m. The sintered teak activated charcoal had crystallinity degree of 78.29% with I-V meter pattern in sigmoid shape and the potentiometer response formed a slope approaching the Nerst factors. Nano carbon produced from lignocellulose is a semiconductor and more suitably use for biosensors, particularly the one derived from teak wood.